Jaundice: A Comprehensive Review (Homoeopathy for All, 2024)
Jaundice, derived from the French  word "jaune," meaning yellow, is  a common medical condition that  can occur in individuals of all ages.  It results from an imbalance in  bilirubin metabolism due to various  pathological processes affecting the  liver, biliary tract, or red blood cells.  Bilirubin, a yellow pigment derived  from the breakdown of heme,  accumulates in the blood and tissues  when its production or clearance is  disrupted, leading to Jaundice. While neonatal Jaundice is  often benign, Jaundice in adults  usually indicates a significant  underlying condition. A systematic  understanding of its pathophysiology  and causes is crucial for appropriate  diagnosis and treatment.
Keywords: 354 million; preterm infants